PTU-258 Prevalence and severity of pre-pouch ileitis: a distinct disease entity or a manifestation of refractory pouchitis?. (22nd June 2015) - Samaan, MA; de Jong, D; Sahami, S; Morgan, S; Fragkos, K; Subramaniam, S; Kok, K; Makanyanga, J; Barnova, I; Saravanapavan, H; Parisi, I; Di Caro, S; et al.
Abstract : Introduction: Pre-pouch ileitis (PI) is a complication that can occur after panproctocolectomy and ileal pouch-anal anastomosis (IPAA) for ulcerative colitis (UC). It is characterised by inflammation of pre-pouch ileum in the afferent limb of the pouch. Our aims were to assess the prevalence of PI as well as to identify predictive factors and investigate the medications needed for its management. Method: Data on 546 patients who underwent IPAA for UC was retrospectively collected from three tertiary inflammatory bowel disease (IBD) referral centres. Data was collected from sites in the Netherlands (Academic Medical Centre, Amsterdam), Belgium (Leuven University Hospital) and England (University College London Hospital). PI was considered present if there was endoscopic, as well as histological inflammation in the afferent limb. Results: PI was present in 33/546 (6%) UC patients, all of these had concurrent pouchitis. 144 (26%) patients had pouchitis without PI. 369 (68%) patients did not have any inflammatory pouch problems. Rates of requiring potent immunosupressive treatment were higher amongst patients with PI than those with pouchitis alone. Patients who went on to develop PI were significantly younger at the time of their UC diagnosis. PSC was significantly more common in patients with PI than those with pouchitis alone. Conclusion: PI is a much less common and more treatment refractory condition than pouchitis alone. Pouchoscopy should be considered in any patient with symptoms of pouchitis. This should include careful endoscopic evaluation of the afferent pouch limb as well as biopsies of the pre-pouch ileum. Once a diagnosis of PI is made, clinicians should commence immunomodulatory therapy early in the disease course and consider escalating to an anti-TNF if this proves ineffective. Disclosure of interest: None Declared.